(untitled) (Research, Society and Development, 2022)
In recent years, a huge variety of Augmented Reality (AR)-based applications have been developed for use on mobile devices. This technology has also been sought by companies, which have envisioned the possibility of obtaining cost savings in several activities, such as maintenance tasks. By evaluating publications and commercial applications related to this specific topic, some initiatives that integrate some technologies are perceived, without exploring all possible benefits. The objective of this work is the implementation of a new framework based on augmented reality, geographical data and image recognition on mobile devices, in order to allow a user to receive the identification of a desired object directly on the screen of his smartphone, as well as additional information to assist his tasks of interacting with an object. A systematic review was carried out to compare approaches already implemented that could contribute to the development of the solution. Tests were also carried out in a commercial application, and case studies related to this theme were evaluated. The framework proposal was then developed and validated by a proof of concept, applying the system to maintenance activities performed by field technicians working for a Telecommunications company. The image recognition worked properly, with the correct identification of the georeferenced object and displaying the requested information through AR. It was verified, therefore, that the proposed application is valid for use in maintenance tasks in the field and can reduce the average maintenance time of each customer and provide greater accuracy of the information used by the technicians.